Resource Allocation Decisions in Audit Engagements* - HACKENBRACK, KARL; KNECHEL, W. ROBERT (Contemporary Accounting Research, 1997)
Abstract. We examine the empirical relationship between auditors' resource allocations and selected engagement characteristics. Our measure of resources is hours of grades of labor (partner, manager, etc.) “charged” to audit activities (planning, internal control evaluation, etc.). Engagement characteristics examined are client size, industry affiliation, client complexity, risk, auditor provision of management advisory services to the auditee, and degree of control reliance. The data were obtained from publicly available sources and a survey developed and administered by an international public accounting firm. We find the cross‐sectional variation in the labor charged to various audit activities can be explained by engagement characteristics found to be important in prior studies on audit fees, total labor inputs, and the mix of labor inputs. Measures of client size, industry, complexity, risk, and services provided are associated with changes in the allocation of labor among audit activities. We find no substitution of internal control review/testing for substantive testing on reliance audits. Task assignments vary by rank. Measures of client size, complexity, risk, and services provided are associated with activity‐specific changes in the labor mix.